Pengembangan Program Pencegahan dan Penanganan Kekerasan di SMA Negeri 1 Kersana, Kabupaten Brebes - Muamar Riza Pahlevi; Fajar Sigit Kusumaja; Faizal Yudhi Nugroho; Labib Fahmi (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
The phenomenon of student brawls has become a source of pride for those with violent tendencies, especially among students. As a result, the phenomenon of student brawls in Indonesia has recently become commonplace. In fact, these brawls have shifted from mere physical fights to violent acts connected directly to social media (live streaming). SMAN 1 Kersana, as a school that is concerned about this phenomenon, has taken anticipatory steps to prevent its students from becoming victims or perpetrators of violence or bullying. One of these measures is by holding In-House Training (IHT) attended by all teachers and staff at the school. After the IHT, there are also follow-ups as concrete steps from the implementation of IHT to develop programs for preventing and handling violence. An understanding of the laws related to acts of violence is mandatory for all parties involved. Furthermore, synergy between all parties, between the school, the school committee, and parents of students is one of the keys to preventing and handling violence at SMAN 1 Kersana.